PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PT. IMPORTIR WARISAN PRATAMA - Falendra,; Realize, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
This research has mainly aimed to know and analyze the influence of service quality, and product quality towards customer loyalty. Sample in this research were taken using purposive sampling method, and data collecting technique using survey method, through questionnaire. Sample size taken 200 respondent or participant. The result of this research gave predictive regression as,Y = 2.175 - 0.050X1 + 1.019X2. The usage of regression formula can be done as all of classical assumption test had been through and qualified. Validity test and reliability test has be done to get qualified data and make sure that  data get properly conducted and accurately to this research. All over the test shown that service quality has not significance influenced at the level of significance 0.666 > 0.05 it means that 1st hypotheses in this research was unproven or rejected. The result for variable product quality has significance influenced towards customer loyalty . it was has a level of significance at 0.000, it means that 2nd hypotheses in this research was proved, or accepted. Meanwhile result for simultaneous test shown that service quality, product quality have significance influenced towards customer loyalty. It has been proved at the level of significance 0.000 < 0.05, It menas that 3rd hypotheses can be proved, or accepted. Amount of supporting of these two variables which is service quality, and product quality  in giving impact on this research was 63.4% and the rest 36.6% was influenced by others variabes.